2008
DOI: 10.1177/0022219407313587
|View full text |Cite
|
Sign up to set email alerts
|

Indexing Response to Intervention

Abstract: In this study, response to intervention and stability of reading performance of 41 kindergarten children identified as at risk of reading difficulty were evaluated from kindergarten through third grade. All students were assessed in the fall of each academic year to evaluate need for intervention, and students who fell below the 30th percentile on criterion measures received small-group supplemental intervention. Measures included a combination of commercial normative referenced measures and specific skill and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 29 publications
(60 reference statements)
2
54
0
2
Order By: Relevance
“…Verhoeven and Van Leeuwe (2009) have previously evidenced such stability in reading development in later phases. To our knowledge, however, the current study was the first to show that stability in individual differences of reading development has already been established during, instead of after, the fundamental processes involved in mastering the alphabetic principle (see also Caravolas et al, 2013; Simmons et al, 2008; Steacy et al, 2014). The high relation of the curriculum embedded word decoding assessments with the standardized word decoding measure after 5 months indicates that the curriculum embedded measurement was an adequate way of assessing children’s performances.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Verhoeven and Van Leeuwe (2009) have previously evidenced such stability in reading development in later phases. To our knowledge, however, the current study was the first to show that stability in individual differences of reading development has already been established during, instead of after, the fundamental processes involved in mastering the alphabetic principle (see also Caravolas et al, 2013; Simmons et al, 2008; Steacy et al, 2014). The high relation of the curriculum embedded word decoding assessments with the standardized word decoding measure after 5 months indicates that the curriculum embedded measurement was an adequate way of assessing children’s performances.…”
Section: Discussionmentioning
confidence: 63%
“…Longitudinal reading studies in both transparent (e.g., Bast & Reitsma, 1998; Verhoeven & Van Leeuwe, 2009) and more opaque orthographies (e.g., Caravolas, Lervåg, Defior, Málkova, & Hulme, 2013; Juel, 1988; Simmons et al, 2008; Steacy, Kirby, Parrila, & Compton, 2014) evidenced high individual stability in reading development over time. However, reported stability in these studies typically refers to the development that was observed after, instead of during, the first months of reading instruction during which fundamental word decoding skills are mastered.…”
Section: Introductionmentioning
confidence: 99%
“…Positive results have been reported by a number of experimental and quasi-experimental studies evaluating outcomes across two or more increasingly intensive tiers of reading intervention (Coyne, Kame’enui, Simmons, & Harn, 2004; Kamps et al, 2008; Mathes et al, 2005; O’Connor, Fulmer, Harty, & Bell, 2005; Simmons et al, 2008; Vadasy, Sanders, Peyton, & Jenkins, 2002; Vaughn et al, 2009). There have been fewer studies evaluating outcomes for primary-grade students who receive intensive intervention (usually Tier 3 in an RTI context) after demonstrating inadequate response in Tiers 1 and 2.…”
Section: Effects Of Reading Intervention In the Primary Gradesmentioning
confidence: 99%
“…This work has led to the identification of children at risk for reading disabilities (RD) as early as kindergarten or first grade and to the development of effective intervention programs (Denton & Mathes, 2003; Foorman, Francis, Fletcher, Schatschneider & Mehta, 1998; Simmons, Coyne, Kwok, McDonagh, Harm, & Kame'enui, 2008). Despite progress, at least one group of children is routinely missed in this process.…”
mentioning
confidence: 99%